The Checklist of Sicilian Macrofungi: Second Edition - Valeria Ferraro; Giuseppe Venturella; Fortunato Cirlincione; Giulia Mirabile; Maria Letizia Gargano; Pasqualina Colasuonno (Journal of Fungi, 2022)
Approximately 30 years after the publication of the first Sicilian checklist of macrofungi, a new updated version is presented here. The census of macromycetes was carried out through periodic observations in different agricultural and forest ecosystems, in urban areas, in public and private gardens, and in botanical gardens. The 1919 infraspecific taxa included in 508 genera belonging to 152 families were collected in the Sicilian territory. Ectomycorrhizal fungi are the most represented ecological category, followed by saprotrophs on wood, saprotrophs on litter, and terricolous saprotrophs. The interest in this rich group of organisms is evidenced by the nutritional and therapeutic value of a high percentage of species. The actions linked to the National Recovery and Resilience Plan and The Network for the Study of Mycological Diversity will further increase the number of macrofungi for Sicily in the future.